On a New Class of p-Valent Meromorphic Functions Defined in Conic Domains - Mohammed Ali Alamri; Maslina Darus (The Scientific World Journal)
We define a new class of multivalent meromorphic functions using the generalised hypergeometric function. We derived this class related to conic domain. It is also shown that this new class of functions, under certain conditions, becomes a class of starlike functions. Some results on inclusion and closure properties are also derived.